Wheat-market Flows in the Punjab (The Pakistan Development Review, 1984)
The first of two articles on the operation of the wheat market in Pakistan, the present article describes the magnitude and composition of wheat flows between farmers, middlemen and consumers in the Punjab. The flows emanating from the agricultural sector and those moving from various sources of supply to consumers have been separately illustrated in two diagrams. A wheat trade table shows the volumes of wheat handled by traders and the position which groups of traders assume in the wheat-trade chain. Further, a brief account is given of the activities of these groups of traders.